An exploration of teachers’ attributions for the causes of emotionally based school avoidance - Devine, Emma (2021)
Background School attendance issues are well-researched and acknowledged internationally as an area of concern for schools (Gren-Landell, 2021). Poor school attendance is associated with negative academic, social, and mental health outcomes (Ingul, Havik, & Heyne, 2019). Emotionally based school avoidance (EBSA) is a form of school attendance difficulty, wherein young people experience emotional distress related to school attendance which can result in prolonged absences (West Sussex Educational Psychology Service, 2018).